Evaluation of Foliar Applications at Different Growth Stages and Soil Amendment for Management of Karnal Bunt Disease in Wheat - ANUJA GUPTA; ASHWANI KUMAR; RAVINDRA KUMAR; KUMKUM VERMA (Seed Research, 2026)
In a field trial, foliar application of 0.1% propiconazole at different growth stages and soil amendment with Trichoderma viride were evaluated for management of Karnal bunt disease in wheat cv. HD 2967. Foliar application of propiconazole at different growth stages from 5% ear emergence to anthesis initiation and completion had significant effect on the disease incidence. Two foliar application of 0.1% propiconazole 95% EC at anthesis initiation and completion were effective in reducing the incidence of KB disease (0.027%) significantly as against control (0.135%) i.e. by 80.0%. Soil amendment with Trichoderma viride @ 2Kg/acre twice at 45 and 75 DAS reduced the disease incidence by 46.2% but these treatments had insignificant effect on test weight.